ROLE OF HR TECHNOLOGY AND TRAINING FOR THE DEVELOPMENT OF EMPLOYEES - Batool, Narjis; Hussain, Sajid; Baqir, Muhammad; Islam, K. M. Anwarul; Hanif, Muhammad (International Journal of Business and Management Future, 2021)
The purpose of this article is to explore the factors and importance of training for developing the employees and focus that how HR technology and e. practices help the HR consultants to make the training more efficient, and what type of technology used in training, and how to improve the training that helps in employees development. The data collection is done by online questionnaire. For this study, 305 respondents fill the questionnaire, and for data, use the primary data. For the imperial foundation of this article, we use the PLS software for analysis. The analysis found that the training plays an essential role in developing the employees. There are positive responses of people about the role of technology and training in organizations. Many employees agree that they need training in the organization to benefit both employees and the company. For this study, we collect the data from different responses and use the convenient approach. This study’s challenge is what types of technology improve the quality of training and how employees understand it easily. Training the employees becomes more proactive and how they influence the activity. JEL Classification Codes: O15, N7, P36, J54.